Bioactivities of major constituents isolated from Angelica sinensis (Danggui) - Lin Bi-Fong; Chao Wen-Wan (BMC, 2011)
Abstract Danggui, also known as Angelica sinensis (Oliv.) Diels (Apiaceae), has been used in Chinese medicine to treat menstrual disorders. Over 70 compounds have been isolated and identified from Danggui. The main chemical constituents of Angelica roots include ferulic acid, Z-ligustilide, butylidenephthalide and various polysaccharides. Among these compounds, ferulic acid exhibits many bioactivities especially anti-inflammatory and immunostimulatory effects; Z-ligustilide exerts anti-inflammatory, anti-cancer, neuroprotective and anti-hepatotoxic effects; n-butylidenephthalide exerts anti-inflammatory, anti-cancer and anti-cardiovascular effects.